Multiple fan-beam optical tomography: Modelling techniques - Ruzairi, Abdul Rahim; Leong, L. Chen; Chan, K. San; Mohd Hafiz, Fazalul Rahiman; Pang, J. Fea (MDPI Publishing, 2010)
Link to publisher's homepage at http://www.mdpi.com/